2011
DOI: 10.1007/s00128-011-0303-2
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Geochemistry of Abandoned Flotation Tailing Reservior from the Tonglvshan Fe-Cu Sulfide Mine in Daye, Central China

Abstract: This study investigated metals of tailings from Tonglvshan mine in Daye and assessed the effect of metal contamination in water and sediment near the tailing reservoir. The concentration of copper, lead, zinc, cadmium, chromium and nickel was measured in deposit samples taken from a profile in an abandoned flotation tailing reservoir, as well as in water and sediment samples near the reservoir. The results of this study indicate that copper concentration ranges from 780 to 4390 mg/kg, 2-10 times higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…This HDS process requires increasing the pH with hydrated lime and subsequently adding iron salts to form precipitates with As. The precipitate residue generally contains high contents of Cu, Pb, Zn, Ca, Cd, Fe, and As. , To determine the metal content in the solid waste, triplicate samples were freeze-dried and were digested with a microwave digestion system (MARS, CEM Corporation, U.S.) …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This HDS process requires increasing the pH with hydrated lime and subsequently adding iron salts to form precipitates with As. The precipitate residue generally contains high contents of Cu, Pb, Zn, Ca, Cd, Fe, and As. , To determine the metal content in the solid waste, triplicate samples were freeze-dried and were digested with a microwave digestion system (MARS, CEM Corporation, U.S.) …”
Section: Materials and Methodsmentioning
confidence: 99%
“…The precipitate residue generally contains high contents of Cu, Pb, Zn, Ca, Cd, Fe, and As. 17,18 To determine the metal content in the solid waste, triplicate samples were freeze-dried and were digested with a microwave digestion system (MARS, CEM Corporation, U.S.). 19 Three bacteria strains from different genera, Pantoea sp.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The change patterns in the three parts of Daye Lake were similar (Figure 4) Most of the trace metal in Daye Lake was from mining waste water (Guo et al, 2011). By 2002, 72% of the mine resources were already exploited.…”
Section: Health Risk Changes In the Past Ten Yearsmentioning
confidence: 82%
“…Extensive mining operations over the years have revealed that Cd, Cr, Pb, and As pose health risks to humans, with soil ingestion representing a signi cant pathway of exposure (Guo et al, 2017;Yin et al, 2012). Previous studies suggested that these HMs originate not only from natural sources but also from mining activities, tra c emissions, and agricultural practices (Guo et al, 2011;Xiao et al, 2017). However, although prior research has con rmed HM contamination in local soils due to mining and metallurgy activities, few studies have attempted to delineate the contribution of these sources to potential health risks.…”
Section: Introductionmentioning
confidence: 99%